PSEUDOANGIOMATOUS STROMAL HYPERPLASIA OF BREAST: A CASE REPORT - Prasad, Sachin N.; Houserkova, Dana; Svach, Ivan; Zlamalova, Nora; Kucerova, Ladislava; Cwiertka, Karel (Biomedical papers, 2008)
Aim: To present a case of pseudoangiomatous stromal hyperplasia (PASH) and its findings under 1. mammography - MG, 2. ultrasonography - USG and 3. magnetic resonance imaging - MRI.Materials and methods: A woman 39 years of age with a history of mass in her right breast of 3 months duration was subjected to a routine examination of the mass using MG & USG. According to the modality findings a core cut biopsy was done following which the samples were send for histological analysis. Later, MRI was done as advocated by the surgeon to get a better picture of the extent of the lesion prior to surgery.Results: Bilateral mammogram views revealed in the patient's right breast a huge well-bordered tumour of lobulated contour without halo sign. Sonography revealed a big well-demarcated tumour in the central part of the right breast which was cystic and lobulated in shape. Histological analysis of the sample confirmed pseudoangiomatous stromal hyperplasia (PASH). MRI under a breast array coil revealed a mass of 85x75x35mm in the right breast. Finally, based on the clinical, radiological and histological report the mass was diagnosed as benign and despite the massive size of the mass, tumour excision alone was done and not mastectomy. The right breast after the huge tumour excision was almost normal in size compared to the left.Conclusion: PASH should be included in the differential diagnosis of a circumscribed or partially circumscribed mass, especially in the pre-menopausal female population. These benign masses often grow over time and can recur locally. Radiological diagnosis of PASH is usually done by MG and USG followed by core cut biopsy for histological analysis. However great the mass is, excision only of the tumor mass is recommended and not mastectomy.
Keywords: Keywords: Breast masses/Nodular tumour/Pseudoangiomatous stromal hyperplasia